Phosphorus Availability Promotes Bacterial DOC-Mineralization, but Not Cumulative CO2-Production - Allesson, Lina; Andersen, Tom; Dörsch, Peter; Eiler, Alexander; Wei, Jing; Hessen, Dag O. (Frontiers in Microbiology, 2020)
The current trend of increasing input of terrestrially derived dissolved organic carbon (DOC) to boreal freshwater systems is causing increased levels of carbon dioxide (CO2) supersaturation and degassing. Phosphorus (P) is often the most limiting nutrient for bacterial growth and would thus be expected to increase overall mineralization rates and CO2 production. However, high carbon (C) to P ratios of terrestrially derived DOC could also cause elevated cell-specific respiration of the excess C in heterotrophic bacteria. Using data from a survey of 75 Scandinavian lakes along an ecosystem gradient of DOC, we estimated in situ CO2 production rates. These rates showed a unimodal response with DOC-specific CO2 production negatively related to DOC:total phosphorus (TP) ratio, and a turning point at 5 mg C L−1, indicating higher DOC turnover rates in productive than in unproductive lakes. To further assess the dependency of bacterial respiration (BR) on DOC and P, we monitored CO2 production in incubations of water with a gradient of DOC crossed with two levels of inorganic P. Finally, we crossed DOC and P with a temperature gradient to test the temperature dependency of respiration rates [as oxygen (O2) consumption]. While total CO2 production seemed to be unaffected by P additions, respiration rates, and growth yields, as estimated by ribosomal gene copy numbers, suggest increased bacterial growth and decreased cell-specific respiration under non-limited P conditions. Respiration rates showed a sigmoid response to increasing DOC availability reaching a plateau at about 20 mg C L−1 of initial DOC concentrations. In addition to these P and DOC level effects, respiration rates responded in a non-monotonic fashion to temperature with an increase in respiration rates by a factor of 2.6 (±0.2) from 15 to 25°C and a decrease above 30°C. The combined results from the survey and experiments highlight DOC as the major determinant of CO2 production in boreal lakes, with P and temperature as significant modulators of respiration kinetics.